ANALISA PENYEBAB TINGGINYA NILAI CACAT DAN PENURUNAN KUALITAS KOPI GAYO MENGGUNAKAN DIAGRAM FISHBONE - Hasni, Dian; Fithriyyah, Alya; Zahira, Anggun; Rizkina, Dini Tria; Rizqi, Muhammad; Sitepu, Syawal; Muzakki, T. Nabil; Suhaila, Widya (Politeknik ATI Padang, 2020)
Coffee is the center of community activity in the Gayo Highlands (DTG). Coffee industry activities from upstream to downstream are the economic center of the DTG community. Therefore, consistent productivity and quality must continue to be considered, maintained and improved so that the selling power of coffee from DTG remains good and is expected to remain good on an ongoing basis. Increasing coffee productivity must also be in line with local wisdom, climate change and environmental sustainability. This study aims to examine the main causes that influence the productivity and marketability of Gayo coffee in line with local wisdom, climate change and environmental sustainability. Furthermore, this research tries to provide an action plan that is in line with the problems that have been identified. The results of the literature review concluded that there are structured problems in increasing coffee productivity related to the age of coffee plants, farmers' understanding, conditions of planting areas, modernization of equipment and quality measurement methods.